2019
DOI: 10.3389/fvets.2019.00264
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dog Owner Concern Regarding Peri-operative Nausea and Vomiting and Willingness to Pay for Anti-emetic Treatment

Abstract: Objective: The objective of this study was to assess dog owners' concern regarding peri-operative nausea and vomiting, and their willingness to pay for treatment. Design: Descriptive survey. Sample: A survey was administered to 104 dog owning clients with non-emergent surgical (52) or non-surgical (52) appointments at a University teaching hospital. Procedure: Descriptive statistics were calculated. A Mann-Whitney U … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…(2019) also determined that many canine owners are aware of the discomfort and negative in uence of nausea on animal welfare and would accept higher costs and longer hospital stays in return for an effective relief for their pets. 35 Golden Retriever (n = 4) and mixed-breed dogs (n = 2) were most likely to have a diagnosis of 'vestibular syndrome' in this case series. Bongartz et al (2020) also found mixed-breed dogs (15.1%) to be most likely affected.…”
Section: Discussionmentioning
confidence: 78%
“…(2019) also determined that many canine owners are aware of the discomfort and negative in uence of nausea on animal welfare and would accept higher costs and longer hospital stays in return for an effective relief for their pets. 35 Golden Retriever (n = 4) and mixed-breed dogs (n = 2) were most likely to have a diagnosis of 'vestibular syndrome' in this case series. Bongartz et al (2020) also found mixed-breed dogs (15.1%) to be most likely affected.…”
Section: Discussionmentioning
confidence: 78%
“…Research has shown that pet owners are willing to pay more, arrive earlier, and wait longer to prevent their pets from vomiting and feeling nauseated. 15 An ideal premedication protocol would be one that provides adequate pain control and sedation while decreasing the frequency of vomiting and nausea. Two different antiemetics-maropitant and ondansetron-are commonly used in dogs.…”
Section: S41mentioning
confidence: 99%
“…A recent study 9 Low incidence of postoperative nausea, vomiting, regurgitation, and aspiration pneumonia in geriatric dogs receiving maropitant, famotidine, and fentanyl as part of an anesthesia protocol Ashley L. Moyer, VMD 1 *; Talon S. McKee 2 ; Philip J. Bergman, DVM, PhD 2 ; Arathi Vinayak, DVM 1 revealed an incidence of PONV in 50% of dogs undergoing routine ovariohysterectomy, and there is an emerging clinical interest in reducing PONV in veterinary patients. 10 However, most previous studies 2,11 have focused on PORV due to the objective nature of these events.…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%